DESIGN AND COMPUTATIONAL FLOW ANALYSIS ON SAVONIOUS WIND TURBINE - SWARNAKIRAN.S; GANESH PAWAR.R; GNANESH.N (International Journal of Innovations in Engineering Research and Technology, 2021)
The principle of wind turbine uses wind kinetic energy to electric power. We observed that the turbine efficiency mainly dependent on parameters like material selection and design criteria. Since here we have mainly focused on turbine for low wind speed, which is of Savonious wind turbine. The parameters affecting the Savonious wind turbine are aspect ratio, primary overlap ratio and secondary overlap ratio. To improve the efficiency of the turbine we have used the maglev phenomenon. The design is small and robust to be placed in a tool post, to obtain available energy from it. Since we make use of Savonious type of blade it is one of the simplest turbine. From the top view it would look like “S-shape” cross-section. Because of its curvature, experiences less drag when moving against the wind.The flow analysis is done by using ANSYSIS WORKBENCH V14.5.